Pengaruh Model Pembelajaran Project Based Learning Berbasis Science, Technology, Engineering, Art, And Mathematics Terhadap Hasil Belajar Siswa Pada Materi Bangun Ruang Kelas V SDN Blega 2 - Sakdiyah, Siti Halimatus; Wulandari, Rika (JOURNAL OF EDUCATION FOR ALL, 2024)
This research aims to determine the influence produced by the STEAM based PJBL learning model on student learning outcomes. This research was conducted on elementary school students in Desa Blega, Kecamatan Blega, Kabupaten Bangkalan, Provinsi Jawa Timur. This type of research uses quantitative research, with a One Group Pretest Posttest Design research design. The population in this study was 39 students with a sampling technique, namely saturated samples. The sample in this study was 39 class V students at SDN Blega 2, consisting of 16 boys and 23 girls. Data collection techniques in this research used observation, questionnaires and tests. The data analysis techniques used are research instrument tests (validity, reliability, level of difficulty, and distinguishing power), normality tests, and t tests as hypothesis tests. The research results show that tcount (-3,824) < ttable (-2,024), and the significance value is 0,00 < 0,05 so that H0 is rejected and Ha is accepted. This means that there is a significant difference between learning outcomes before and after implementing the STEAM-based PJBL learning model. So it can be concluded that the STEAM-based PJBL learning model has a significant influence on student learning outcomes.